One-Pot Multicomponent Synthesis of Diversely Substituted 2-Aminopyrroles. A Short General Synthesis of Rigidins A, B, C and D - Frolova, Liliya V. (2011)
[Image: see text] Privileged medicinal scaffolds based on the structures of tetra- and penta-substituted 2-aminopyrroles were prepared via one-pot multicomponent reactions of structurally diverse aldehydes and N-(aryl-, hetaryl-, alkyl-sulfonamido)-acetophenones with activated methylene compounds. This methodology was used in a four-step synthesis of alkaloids rigidins A, B, C and D in overall yields 61%, 58%, 60% and 53%, respectively. Of these, rigidins B, C and D were synthesized for the first time.